Legal ideas of Kazan University professors A.T. Bazhanov and N.S. Zakharov: Problems of consolidating the rule of law and order - I.A. Tarkhanov; N.G. Muratova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The research works of A.T. Bazhanov and N.S. Zakharov, two professors of Kazan University, were discussed. They studied the emergence and development of state legislation aimed to ensure the law and order at various historical stages. The importance of A.T. Bazhanov’s ideas about the bodies of the Paris Commune of 1871 and its historical lessons for the development of foreign and Russian legislation was emphasized. The researcher analyzed the experience of development of judicial institutions and focused on the role of examining judges, magistrate judges, and freedom of judicial protection in the criminal process. Some of them are still crucial in the modern period. In the Republic of Tatarstan, magistrate judges appointed by the State Council successfully perform their duties. N.S. Zakharov singled out certain stages in the formation of Russian revolutionary legislation during the 1920s. He also paid a considerable attention to criminal punishment. Both professors were concerned with strengthening the rule of law and order, which was promoted in their lectures delivered to many generations of students. They updated their views with time and in the process of law enforcement advance. We investigated the historical events described in the works of these professors. Their conclusions are of practical use in modern legislation. The need to preserve traditions in further formation and development of Russian law was proved.